Fluid-assisted metasomatic processes on planetary bodies: Evidence from vestan lithologies. (1st January 2023) - Shisseh, T.; Chennaoui Aoudjehane, H.; Barrat, J.A.; Zanda, B.; Hewins, R.H.; Agee, C.B.; Folco, L.; Jacquet, E.; Pont, S.
Abstract: The mechanisms responsible for the formation of Fe-rich, metasomatic features in eucrites and their debris in howardites are yet controversial. In this study, secondary phases found in polymict eucrite NWA (Northwest Africa) 11911, howardite NWA 1664, monomict eucrite NWA 8675 and unbrecciated basaltic eucrite NWA 13269 were investigated to elucidate their origin and history of formation. Among them, NWA 11911 is the only rock that displays widespread Fe-enrichment near fractures in unequilibrated and slightly equilibrated basaltic clasts and pyroxene fragments. Fayalitic olivine veinlets with various textures, thicknesses and compositions (Fa64-82 ) are detected in unequilibrated pyroxenes in NWA 11911, NWA 1664 and NWA 8675. Neighbouring Fe-enriched pyroxene is also Al-depleted compared to magmatic pyroxene (Al2 O3 = ∼0.3 wt%). NWA 13269 contains Ca-rich plagioclase (An97-98 ) veinlets associated with Cr-spinel, but apparently no Fe-enrichment in pyroxene nor ferroan olivine despite a careful search. Olivine veinlets have been also detected in equilibrated pyroxene in NWA 11911. Our observations support the fluid-assisted metasomatism scenario that involves the circulation of hydrothermal fluids throughout the fractures of eucritic material.